Ilang Eksplorasyon sa Pag-aaral ng Kulturang Popular sa Filipinas - Sánchez, Louie Jon A. (Archīum Ateneo, 2024)
Pacing Caroline Hau (2002), this essay explores the historical and intellectual specificities of Cultural Studies and the study of Popular Culture in the Philippines, and situates them in the author’s recent study of the cultural history of the teleserye, the Filipino TV soap opera. While the essay assumes that much of the key ideas and paradigms of Western Cultural Studies have been adopted in the country, the ethos of the local field may also be traced back to the works of patriots José Rizal and Isabelo delos Reyes. The projects of the two have been continued by intellectuals and scholars who emerged during the 1960s to the 1970s and formulated more postcolonial approaches to the study of Philippine culture. Moreover, the essay comments on the importance and role of interdisciplinarity in the emergence of Cultural Studies and the study of Popular Culture in the Philippines.